Inbreeding depression on growth traits of Iranian Lori sheep - Yeganehpur, Zahra; Roshanfekr, Hedayatollah; Fayazi, Jamal; Beyranvand, Mir Hossein (Revista Colombiana de Ciencias Pecuarias, 2016)
<!-- [if gte mso 9]> 15.0 <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--><!--StartFragment--> Lori sheep is an Iranian heavy breed known for its superiority in terms of disease resistance, adaptability to the mountainous west of the country and meat production potential. Objective: to estimate and compare the inbreeding coefficient in Lori sheep, and its impact on growth traits. Methods: data and pedigree information were collected in Lorestan Agricultural and Natural Resources Research Center, west of Iran, during 2001-2010. Traits included were birth weight (BW), weaning weight (WW), 6-month weight (6MW) and 9-month weight (9MW). The inbreeding coefficient estimation was carried out through the CFC software, and quantification of individual inbreeding regression on the characteristics was conducted using The Wombat software. All animals were divided into four categories according to the inbreeding coefficients obtained from their pedigree: the first category included non-inbred animals (F = 0%); and the second, third, and fourth categories included inbred animals as 0 < F ≤ 0.10, 0.10 < F ≤ 0.20, and F > 0.20, respectively. Results: inbreeding coefficients were 0.69% and 2.24% in the entire population and inbred population, respectively. Inbreeding regression for BW, WW, 6 MW and 9 MW were estimated as +4.5, -10.3, -76.3, and -77.4 g, respectively. The inbreeding trend was positive and significant for the whole population (0.215; p < 0.001), but not significant for the inbred population. Conclusion: these results confirm a low level of inbreeding and suggest that direct controlled mating could be an appropriate method to avoid inbreeding depression. <!--EndFragment-->